Don't copy that: Security printing and the making of high-tech paper. (August 2019) - Kaminska, Aleksandra
Printing is not a new media technology, but it is continuously being renewed. In this sense, it is an example of novelty going largely unnoticed, woven into the quotidian and ordinary in unassuming ways. One reason for this is the incomplete way we tell the story of printed paper, which privileges narratives of readings, access, and dissemination. To complicate the way media scholars think printing, this article turns to the case of security printing, which produces objects like banknotes and passports that circulate with trust and authority. Here, printing emerges through the specific need to print securely, offering a narrative based on the need for order and protection. The work of security printing, always straddling between art and science, produces artefacts understood as authentic copies. Such a transformation of paper into valuable object relies on the technical artistry of the security printer, who sets the aesthetic and material standards of authenticity through physical features like watermarks, engravings, holographs, special substrates, threads, or inks. Drawing on a close reading of informational materials produced by the major actors of today's security printing industry, this article explains how the need to print better than the (counterfeiting) competition fuels the need for novelty in the how of printing. It expands on three guiding principles that work in unison to keep printing on paper new: printing as material science, as complex composition, and as the display of matchless quality. Ultimately, this material quality of securely printed papers helps us think about the new in a way that is not tied up to the digital, so that security printing both complicates the way media scholars engage with printing and offers a reconsideration of the ways we categorize and theorize the differences between media 'old' and 'new'.